2017
DOI: 10.2147/ndt.s147317
|View full text |Cite
|
Sign up to set email alerts
|

Atypical depression: current perspectives

Abstract: The history and present status of the definition, prevalence, neurobiology, and treatment of atypical depression (AD) is presented. The concept of AD has evolved through the years, and currently, in Diagnostic and Statistical Manual of Mental Disorders (DSM), Fifth Edition, the specifier of depressive episode with atypical feature is present for both diagnostic groups, that is, depressive disorders and bipolar and related disorders. This specifier includes mood reactivity, hyperphagia, hypersomnia, leaden para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 87 publications
1
59
0
3
Order By: Relevance
“…Finally, our study has also a translational relevance, since inflammatory markers-and especially CRP levels-have often been associated with atypical depression forms, which are more likely to be resistant to treatment with first-line antidepressants, like selective serotonin reuptake inhibitors (SSRI;Chamberlain et al, 2019;Hickman et al, 2014;Köhler-Forsberg et al, 2017;Mora et al, 2018;Strawbridge et al, 2017). Conversely, other classes of antidepressants like monoamine oxidase inhibitors (MAOI) have been reported to be more effective in this sense (Cleare, Fekadu, & Rane, 2012;Łojko & Rybakowski, 2017), and have also been associated with a reduction of oxidative stress and chronic inflammation levels (Sturza et al, 2019). While in the current study, we could not identify the type of antidepressants used by participants, access to regional drug prescription registries will possibly allow us to investigate separately treatment-resistant and -responsive depression forms in the future.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, our study has also a translational relevance, since inflammatory markers-and especially CRP levels-have often been associated with atypical depression forms, which are more likely to be resistant to treatment with first-line antidepressants, like selective serotonin reuptake inhibitors (SSRI;Chamberlain et al, 2019;Hickman et al, 2014;Köhler-Forsberg et al, 2017;Mora et al, 2018;Strawbridge et al, 2017). Conversely, other classes of antidepressants like monoamine oxidase inhibitors (MAOI) have been reported to be more effective in this sense (Cleare, Fekadu, & Rane, 2012;Łojko & Rybakowski, 2017), and have also been associated with a reduction of oxidative stress and chronic inflammation levels (Sturza et al, 2019). While in the current study, we could not identify the type of antidepressants used by participants, access to regional drug prescription registries will possibly allow us to investigate separately treatment-resistant and -responsive depression forms in the future.…”
Section: Discussionmentioning
confidence: 86%
“…However, MAOIs are no longer widely used, and evidence that patients with atypical depression respond better to MAOIs than to the newer generation medications has been lacking 73 . Moreover, a recent meta-analysis found that atypical depression did not predict or moderate the response to either cognitive behavioral therapy or antidepressant medication 53 .…”
Section: Clinical Subtypesmentioning
confidence: 99%
“…99 In conclusion, beyond the older findings of the superiority of MAOIs compared to TCAs in treating MDD-AF, so far, no specific indications are available to help clinicians in selection among newer antidepressants. 113 However, as associations between atypical depression and bipolarity were found, which can have therapeutic implications, 114 careful information about possible risk factors for bipolarity should be collected in clinical practice before starting treatment when atypical features are present. Likewise, some associations found between atypical depression, overweight/obesity, and resistance to leptine 114,115 suggest that clinicians should consider antidepressants with limited effects on appetite and/body weight when treating patients with MDD-AF.…”
Section: Mdd With Atypical Featuresmentioning
confidence: 99%